Nature-Based Solutions for Resilient Rice Agro-ecosystems: A Review of Ecological Insect Pest Management and Biodiversity Conservation - Ravindra Chandra Joshi; S. Shrivastava; Annamalai Sivapragasam; Anand Prakash (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Nature-based tools restore biodiversity and self-regulating pest control. - Flowering strips and border crops boost beneficial predator populations. - Neem and custard apple biopesticides disrupt pests without toxicity. - Soil biochar and silicon build strong physical barriers in rice plants. - Integrated duck and fish farming suppresses pests while cutting chemical use. ABSTRACTThe Green Revolution expanded global rice production but introduced systemic environmental vulnerabilities by eroding biodiversity and natural pest regulation. This critical review examines the strategic transition from pesticide-intensive cultivation to nature-based solutions (NbS) that prioritize ecological resilience. We synthesize diverse strategies, including ecological engineering, microbial tools, and integrated rice-animal farming, to demonstrate their collective efficacy in maintaining stable yields. Environmental manipulation through flowering strips supports a robust natural enemy complex, including the mirid bug (Cyrtorhinus lividipennis (Reuter)) and the egg parasitoid wasp (Trichogramma japonicum Ashmead). Furthermore, we evaluate the pivotal role of botanical insecticides from the neem tree (Azadirachta indica A. Juss.) and the sugar apple (Annona squamosa L)., alongside soil amendments like biochar, to induce systemic host resistance via silicon-mediated defenses. Crucially, we highlight how microbial biopesticides, including the entomopathogens Bt (Bacillus thuringiensis Berliner), green muscardine fungus (Metarhizium anisopliae (Metschn.) Sorokīn), and specialized granuloviruses, work in synergy with animal co-cultures involving the domestic duck (Anas platyrhynchos domesticus L.) and the common carp (Cyprinus carpio L.). Together, these synchronized interventions establish multi-layered barriers against major pests like the brown planthopper (Nilaparvata lugens (Stål)) and the yellow stemborer (Scirpophaga incertulas (Walker)). By aligning cultural, biochemical, and biological practices, these solutions foster functional biodiversity and self-regulating mechanisms, providing a resilient framework for the long-term sustainability of global rice agriculture amidst shifting climatic challenges.